Sperm whale predator-prey interactions involve chasing and buzzing, but no acoustic stunning - Fais, A; Johnson, M; Wilson, M; Aguilar de Soto, Natacha; Madsen, P T (Scientific Reports, 2016)
The sperm whale carries a hypertrophied nose that generates powerful clicks for long-range echolocation. However, it remains a conundrum how this bizarrely shaped apex predator catches its prey. Several hypotheses have been advanced to propose both active and passive means to acquire prey, including acoustic debilitation of prey with very powerful clicks. Here we test these hypotheses by using sound and movement recording tags in a fine-scale study of buzz sequences to relate the acoustic behaviour of sperm whales with changes in acceleration in their head region during prey capture attempts. We show that in the terminal buzz phase, sperm whales reduce inter-click intervals and estimated source levels by 1-2 orders of magnitude. As a result, received levels at the prey are more than an order of magnitude below levels required for debilitation, precluding acoustic stunning to facilitate prey capture. Rather, buzzing involves high-frequency, low amplitude clicks well suited to provide high-resolution biosonar updates during the last stages of capture. The high temporal resolution helps to guide motor patterns during occasionally prolonged chases in which prey are eventually subdued with the aid of fast jaw movements and/or buccal suction as indicated by acceleration transients (jerks) near the end of buzzes. Field work in Norway was funded by the Carlsberg Foundation and the National Danish Research Council to PTM. The NMFS study was funded by the U.S. Mineral Management Service. MJ is funded by the Marine Alliance for Science and Technology, Scotland, and by a Marie Curie Career Integration Grant. MW was funded by the Danish Council for Independent Research, Natural Science and NAS is currently funded by a EU Horizon 2020 MSC Fellowship. Peer reviewed